ANALISIS PENGARUH RASIO PROFITABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR MIGAS DI BURSA EFEK INDONESIA PERIODE 2007 – 2011 - Sinta Boentoro; Daniel Abnerpratama Pantouw (Jurnal Manajemen, 2015)
Ratio analysis is useful for assessing the company’s financial performance. One type of ratio analysis is the analysis of profitability ratios are useful for analyzing the company's ability to generate profits . This study was conducted to determine whether the profitability ratios have an effect on stock prices . Profitability ratios used in this study is the Return on Sales , Return on Assets and Return on Equity . The method used in this research is the method of panel data, because the data studied is a combination of cross section data and time series . The model used in this study consisted of Pooled Least Square ( PLS ) , Fixed Effect Model ( FEM ) . From the estimation data panel found that Return on Sales , Return on Assets ,and Return on Equity have a significant effect on stock prices . While partially only Return on Assets that have a significant effect on stock prices.